Power output and efficiency of a thermoelectric generator under temperature control. (1st November 2016) - Chen, Wei-Hsin; Wu, Po-Hua; Wang, Xiao-Dong; Lin, Yu-Li
Graphical abstract: Highlights: Power output and efficiency of a thermoelectric generator (TEG) is studied. Temperatures at the module's surfaces are approximated by sinusoidal functions. Mean output power and efficiency are enhanced by the temperature oscillation. The maximum mean efficiency of the TEG in this study is 8.45%. The phase angle of 180° is a feasible operation for maximizing the performance. Abstract: Operation control is an effective way to improve the output power of thermoelectric generators (TEGs). The present study is intended to numerically investigate the power output and efficiency of a TEG and find the operating conditions for maximizing its performance. The temperature distributions at the hot side and cold side surfaces of the TEG are approximated by sinusoidal functions. The influences of the temperature amplitudes at the hot side surface and the cold side surface, the phase angle, and the figure-of-merit (ZT) on the performance of the TEG are analyzed. The predictions indicate that the mean output power and efficiency of the TEG are significantly enhanced by the temperature oscillation, whereas the mean absorbed heat by the TEG is slightly influenced. An increase in the temperature amplitude of the hot side surface and the phase angle can effectively improve the performance. For the phase angle of 0°, a smaller temperature amplitude at the cold side surface renders the better performance compared to that with a larger amplitude. When the ZT value increases from 0.736 to 1.8, the mean efficiency at the phase angle of 180° is amplified by a factor of 1.72, and the maximum mean efficiency is 8.45%. In summary, a larger temperature amplitude at the hot side surface with the phase angle of 180° is a feasible operation for maximizing the performance.